Complexmetric Determination of Chromium(III) from Binary and Ternary Metal Ion Mixture Using 3-Hydroxy-3-p-Nitrophenyltriazene - Kumar Yadav, Vinod; Kumar Paliwal, Krishna; Kumar, Sanjay; Kishore Gupta, Brij; Goswami, A.K.; Purohit, D.N. (Asian Journal of Chemistry, 2010)
A new indicator 3-hydroxy-3-p-toIyI-1-p-nitrophenyItriazene was developed for the simultaneous complexornetric determination of Cr(III) from binary and ternary metal ion mixtures by kinetic masking. The method is simple and efficient for the compIexometric determination of trace amount of Cr(III).